Cytotoxicity Assay of Peripheral Blood Mononuclear Cells (Pbmc) treated with Gynura Procumbens extract / Adderly Izna Isaac - Isaac, Adderly Izna (2016)
Gynura procumbens, or also known as “Sambung nyawa” is a type of herbs that is widely used in South East Asian countries, particularly in Indonesia, Malaysia and Thailand. It is traditionally used for treatment of many diseases such as cancer, kidney diseases, migraine, hypertension and diabetes. The present study was conducted to investigate the cytotoxicity of peripheral blood mononuclear cells (PBMCs) treated with Gynura procumbens extract. PBMCs were separated from whole blood, and 2 x 105 cells/well were cultured and treated with a 0.0 μg/ml, 6.25 μg/ml, 12.5 μg/ml, 25.0 μg/ml, 50.0 μg/ml, 100.0 μg/ml, 200.0 μg/ml, 400.0 μg/ml, 800.0 μg/ml and 1600.0 μg/ml of aqueous and ethanolic extract of Gynura procumbens for a period of 24 hours. 10 μg/ml of lipopolysaccharide(LPS) from Esherichia coli 0157, was treated onto the positive control wells. Result shows that Gynura procumbens extracts, both aqueous and ethanolic, does not cause any significant cytotoxicity effect on PBMC. Most concentrations show more than 80% of the percentage of living cell, thus indicating that concentration ranging from 0.0 μg/mL until 1600.0 μg/mL is safe to be used. The comparison of cytotoxicity effect between aqueous and ethanolic extract also does not give any significant differences. Further study of cytotoxicity of this plant using higher concentration is recommended.